Opinion Mining with Real Time Ontology Streaming Data - Vithya, G.; Naren, J.; Varun, V. (International Journal of Psychosocial Rehabilitation, 2024)
Social networking, the fastest mode of finding individuals with heterogeneous opinions on various issues, is the current trend in today’s world. There are many social networking sites like Facebook, Twitter, etc. where not only information exchange but also sharing opinions happens. Sentiment analysis, or opinion mining, deals with various emotions and its analysis as positive, negative, and neutral due to the mood of a particular individual. The work ultimately focuses on a system built with opinions mined from data extracted live from Twitter. The development in a particular field could be efficiently analyzed based on opinion mining. Extraction of major important features is done with ontologies and its analysis with feature quotient. In the proposed work, all attributes are analyzed and individual scores are allotted.